(3dhGbM GdCfhGQ aj WHbGJ GdCNjGQs - (3YHO GdhgGH Hf CMeO Hf Ydj GdMfaj, fSHg Edj eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO,J (B973 (3g` s
(3BNQgG (B:s
(3JQLeI GdTjN EHQGgje GdbQTj GdOShbj s
(3GdLRA GdChd ef fSNI KGfjIs
(3YdjgG oeWGdYI YHOGdoeYWj GdTGej GdTGaYj SfI (B1062(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B218s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B338 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B466 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B362 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs